(untitled) (Journal of Engineering, 2011)
Experimental research was carried out on eight reinforced concrete beams to study the embedded length of the longitudinal reinforcement. Six beams were casted using self compacted concrete, and the two other beams were casted using normal concrete. The test was carried out on beams subjected to two point loads. The strain and the slip of the main reinforcement have been measured by using grooves placed during casting the beams at certain places. The measured strain used to calculate the longitudinal stresses (bond stress) surrounding the bar reinforcement, The study was investigated the using of self compacted concrete SCC on the embedded length of reinforcing bars, and comparing the results with normal concrete. The test results show that using SCC improve the concrete properties like the compressive strength and the tensile strength which mainly affected the bond strength and the splitting of the concrete cover failure. The testes show that with increasing concrete strength the bond strength increased.